Guided acoustic wave Brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Wittmann, Christoffer; Andersen, Ulrik Lund; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Journal of Physics: Conference Series, 2007)
In silica glass fibers, thermally excited acoustic phonons scatter light into the beam propagating in the forward direction. At acoustic frequencies up to several hundreds of megahertz, the wave vectors of the phonons interacting with the light propagate essentially transversally to the fiber axis. This effect is known as Guided Acoustic Wave Brillouin Scattering (GAWBS) and leads to phase and polarization noise in the guided light. For fiber-based quantum optics experiments, this excess noise is a major limitation. In Photonic Crystal Fibers (PCFs), light is guided by a microstructure simultaneously acting as a 2D transversal phononic crystal which modifies the acoustic noise spectrum. We demonstrate a GAWBS-noise reduction in commercially available PCFs. This gives rise to the prospect of fiber-based quantum optic devices exhibiting less excess noise, thus resulting in higher quantum state purity. Further improvement can be achieved by tailoring the photonic microstructure such that a reduction of phonon noise by design is achieved. © 2007 IOP Publishing Ltd.
Created from Fastlane, Scopus look-up